(untitled) (Medical Forum Monthly, 2024)
Objective: The main objective of the study is to find the frequency of comorbidities in patients presenting with acute coronary syndrome. Study Design: This retrospective study Place and Duration of Study: This study was conducted at the Department of Cardiology, Gajju Khan Medical College, Swabi from June 2022 to June 2023. Methods: Data was collected from 320 acute coronary syndrome patients. Demographic and clinical data were extracted from electronic medical records, including age, gender, past medical history, presenting symptoms, laboratory results, electrocardiogram findings, echocardiography reports, and comorbidities. Results: Data were collected from 320 patients from both genders. Mean age of the patients was 58.9±8.5 years, and there were 65% male and 35% female patients. The most common presenting symptom was chest pain, reported by 85% of patients, followed by shortness of breath (60%) and fatigue (40%). The prevalence of comorbidities among the study population was as, hypertension (70%), dyslipidemia (60%), diabetes mellitus (50%), obesity (40%), chronic kidney disease (25%), and heart failure (20%). Combinations of comorbidities were also observed, with the most common being hypertension and dyslipidemia (50%), followed by hypertension and diabetes mellitus (40%), and dyslipidemia and diabetes mellitus (30%). Conclusion: It is concluded that comorbidities play a substantial role in the presentation, management, and outcomes of acute coronary syndrome. High prevalence rates and distinct patterns of comorbidity combinations underscore the importance of comprehensive risk assessment and personalized treatment approaches for acute coronary syndrome patients.